2017
DOI: 10.1021/acs.joc.7b00948
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Regioselective Mono-Arylation: Quinazolinone as the Inherent Directing Group for C(sp2)–H Activation

Abstract: The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diaryliodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The Pd(II)-catalyzed C4-selective arylation of isoquinolone using symmetrical diaryliodonium tetrafluoroborates was reported by Hong [79]. The reaction was conducted with Pd(OPiv) 2 (10 mol%) as a catalyst in DME at 120 • C for 24 h and the high regioselectivity was consistent with an electrophilic palladation pathway involving a Pd(II/IV) catalytic cycle (Scheme 14) [80]. A radical mechanism was ruled out since the addition of a scavenger in the reaction mixture did not affect the reaction.…”
Section: Introductionmentioning
confidence: 85%
“…The Pd(II)-catalyzed C4-selective arylation of isoquinolone using symmetrical diaryliodonium tetrafluoroborates was reported by Hong [79]. The reaction was conducted with Pd(OPiv) 2 (10 mol%) as a catalyst in DME at 120 • C for 24 h and the high regioselectivity was consistent with an electrophilic palladation pathway involving a Pd(II/IV) catalytic cycle (Scheme 14) [80]. A radical mechanism was ruled out since the addition of a scavenger in the reaction mixture did not affect the reaction.…”
Section: Introductionmentioning
confidence: 85%
“…Mhaske et al . used quinazolinone as a DG in for Pd‐catalyzed C–H arylation to obtain novel quinazolinones of biological interest . These works revealed application prospect of DG in for rapid construction of natural product‐like and drug‐like molecules.…”
Section: Intrinsic Directing Groupsmentioning
confidence: 99%
“…Notably, when the reaction was conducted without base, the yield decreased to 32% in AcOH as the solvent (Table 1, entry 10), which suggested that AcOH played an important role in the reaction (Table 1, entry 1 versus entry 12). 14 We also examined the counteranion effect; the diaryliodonium salt with an anion of OTf gave the best yield of 83% (Table 1, entries 13−15). When we reduced the amounts of diphenyliodonium salt to 2.5 equiv, the isolated yield decreased to 67% (Table 1, entry 16).…”
mentioning
confidence: 99%
“…K 2 HPO 4 was proven to be the best choice, affording 3aa in an excellent yield of 83%. Notably, when the reaction was conducted without base, the yield decreased to 32% in AcOH as the solvent (Table , entry 10), which suggested that AcOH played an important role in the reaction (Table , entry 1 versus entry 12) . We also examined the counteranion effect; the diaryliodonium salt with an anion of OTf gave the best yield of 83% (Table , entries 13–15).…”
mentioning
confidence: 99%